SPECIES COMPOSITION AND GEOGRAPHICAL DISTRIBUTION OF SPECIES OF LOCUST INHABITING KARACHAY-CHERKESSIA - Z. S. Temirlieva (Юг России: экология, развитие)
Aim. The aim of this work was to study the characteristics of the fauna of locusts in Karachay-Cherkessia, as some areas of the region's fauna has not been studied for a long time. Locusts (Acrididae) can be defined as dominant in numbers and biomass, which makes them an important role as herbivores as well as crop pests, so the modern study of locusts is of great interest. Methods. With observations in nature and conducted experiments in the laboratory we have made tests on behavior for five species of locusts (Omocestus haemorrhoidalis Ch., Chorthippus albomarginatus Deg., Chorthippus bigutullus L., Chorthippus apricarius L., Chorthippus mollis Ch.). Results. As a result, the inventory of species composition of locusts inhabiting the territory of Karachay-Cherkessia revealed 53 species belonging to 31 genera. Conclusions. This work is a modern faunal study of locusts inhabiting KarachayCherkessia. It has been identified 53 species of locusts, and data about the fauna group under study was updated. The faunal information is given in compliance with the current level of taxonomic knowledge of the group, and also presents data on the geographic distribution of all known species of the region.